PENGARUH PENGUATAN PENGELOLAAN KEUANGAN DESA DAN OPTIMALISASI PERAN BUMDES TERHADAP KEMANDIRIAN DESA (Studi Pada Desa di Kecamatan Maja Kabupaten Majalengka) - Hani Sri Mulyani; Wulan Riyadi; Faskal Dias Anugrah (Program Studi Akuntansi Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
The purpose of this study was to determine the effect of strengthening village financial management and optimizing the role of BUMDes on village independence (studies in villages in Maja district). This study uses quantitative data and the source of data collection is primary data. Saturated sample becomes a sampling method with descriptive analysis and verification analysis. The population and sample of this study are village heads, village secretaries, and village treasurers in Maja District. In order to obtain 54 processed data. The hypothesis testing method is multiple linear regression with the help of SPSS version 25. The results of this study partially and simultaneously show that Strengthening Village Financial Management and Optimizing the Role of BUMDes have an effect on Village Independence.